(untitled) (Web of Teachers: Inderscience Research, 2026)
This article explores the critical role of teaching methods in enhancing students’ listening and speaking skills, which are essential components of effective communication. It examines various pedagogical approaches, including communicative language teaching, task-based learning, and interactive techniques, highlighting their effectiveness in fostering active engagement and practical use of language. The article also discusses the importance of creating a supportive learning environment that encourages students to practice listening and speaking in real-life contexts. Additionally, it addresses challenges educators face in implementing these methods and provides recommendations for integrating technology and collaborative activities to further enhance skill development.